Mistletoes and epiphytic lichens contribute to litter input in Nothofagus antarctica forests - Soler Esteban, Rosina Matilde; Martínez Pastur, Guillermo José; Lencinas, María Vanessa; Peri, Pablo Luis (Acta Oecologica)
Litter input is one of the key components that define nutrient cycling in forests and the majority of studies only consider the tree components of litterfall. However, epiphytic species can play a crucial role in litter input throughout the growing season. This work evaluates changes in litter production by mistletoe (Misodendrum sp.) and epiphytic lichen (Usnea sp.), related to crown cover in mature unmanaged, second-growth and managed (thinned for silvopastoral use) forests in Tierra del Fuego (Argentina). We used plastic traps to collect litterfall biomass from trees, lichens and mistletoes on a monthly basis over three consecutive years. Tree litter was considerable during autumn (March to May), which is typical of Nothofagus deciduous species in the Southern hemisphere. In contrast, peak litterfall from mistletoes and lichens occurred during spring and summer seasons. Tree litter (1954e3398 kg dry matter ha 1 year 1) was correlated with crown cover gradient being highest in second-growth forests and lowest in thinned sites. While litter input from mistletoes did not vary among forest types (307 e333 kg dry matter ha 1 year 1), lichen litter (11e40 kg dry matter ha 1 year 1) was higher in unmanaged and thinned mature forests despite differences in tree crown cover. Contrary to what we expected, the management practices investigated here did not affect the biomass of canopy communities compared to unmanaged mature forests. Mistletoes and lichens significantly increased the spatial (forest type) and temporal complexity (extended period of falling) of litterfall in Nothofagus antarctica forests. This study provides a starting point to understand the ecological relevance of canopy communities in the Patagonian forests of southern Argentina. Fil: Soler Esteban, Rosina Matilde. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de ...